Intellectual capital disclosure: Scenario of a developing economic - Bhasin, Madan Lal; Bamahros, Hasan Mohammed (ESTACAO VITIVINICOLA NACIONAL DIOS PORTOS, PORTUGAL, 2015)
In the era of information and knowledge, effective use of Intellectual Capital (IC) is the most important factor that determines the success of a business leading to sustainable competitiveness. Value creation has been a concern for many years and companies have always been trying to find out the best ways for its improvement.Thus, IC disclosure (ICD) is becoming a major part of companies‘ value in today‘s knowledge-based economy. Currently, ICD is not compulsory and is done by the companies purely on ―voluntary‖ basis. IC disclosure has become a critical necessity in this new framework.IC measurement, reporting and disclosures in the developing economy are still at a very nascent stage, especially in India.This is an exploratory study of ICD and measurement by the 8 Indian companies over 5-year period, using content analysis and market value added (MVA) as research methodologies.IC is valued at market value (MV) minus book value (BV).The annual reports of the selected companies were collected from their respective web sites.As part of present study, various statistical techniques have been used to analyze the data.The findings show that on an average, the sample companies reported a positive value of IC; significant correlation has been noticed between tangible assets (TA) and net operating profits (NOP).However, no significant difference was found between percentage of IC to MV, and per cent of TA to MV.The study finds wide-disparity, low-level, and purely voluntary nature of the ICD made by the selected companies. Unfortunately, the omission of IC information may adversely influence the quality of decisions made by shareholders, or lead to material misstatements.We recommend to the international accounting bodies, to take the lead by establishing a harmonized ICD standard, and provide guidance to the big listed companies for proper measurement and disclosure of IC, both for internal and external users